Report of a pastoral and fact-finding mission to the Republic of Haiti (Caribbean Conference of Churches BridgetownBB, 1991)
Concludes that the situation in Haiti is one of deep polorisation, widespread fear pervading uncertainty, seething anger, great confusions but nonetheless one of challenge and hope. Details its findings with regard to the following - the international community; the Aristide government; President Aristide; the poor; the political class; the Houses of Parliament; the armed forces; and the churches. Presents a list of recommendations to the sectors and parties involved.
DC